2016
DOI: 10.4238/gmr.15028250
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic variations in the ACLY gene with growth traits in Chinese beef cattle

Abstract: ABSTRACT. ATP citrate lyase (ACLY) is the primary enzyme responsible for the synthesis of cytosolic acetyl-CoA, which is a key precursor of both fatty acid and mevalonate synthesis pathways. Genetic variation of the ACLY gene may influence multiple traits associated with animal production. Here, we identified three non-synonymous mutations in ACLY exons in five beef cattle populations using DNA pool sequencing and high-resolution melting analysis. Results from association analyses revealed that the single nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Recently, Shang et al (2019) revealed that the ACLY gene was responsible for fatness and FA composition traits in Tibetan and Yorkshire Pigs. The ACLY gene was also associated with growth traits and fatty acid content of milk in cattle (Bouwman et al 2013;Li et al 2016). Muñoz et al (2015) detected two single nucleotide polymorphisms (SNPs) in porcine ACLY gene -c.2970T > C and c.*523 T > C. First one is a silent variant located in exon 24, however the second one is located in the 3'-UTR region.…”
Section: Traits Meat Qualitymentioning
confidence: 99%
“…Recently, Shang et al (2019) revealed that the ACLY gene was responsible for fatness and FA composition traits in Tibetan and Yorkshire Pigs. The ACLY gene was also associated with growth traits and fatty acid content of milk in cattle (Bouwman et al 2013;Li et al 2016). Muñoz et al (2015) detected two single nucleotide polymorphisms (SNPs) in porcine ACLY gene -c.2970T > C and c.*523 T > C. First one is a silent variant located in exon 24, however the second one is located in the 3'-UTR region.…”
Section: Traits Meat Qualitymentioning
confidence: 99%